Effect of different flower thinning techniques on annual fluctuation of macro and micronutrients in sweet cherries - Nagy, P. T.; Thurzó, S.; Racskó, J.; Nyéki, J.; Soltész, M.; Szabó, Z. (International Journal of Horticultural Science, 2007)
The seasonal dynamic of macro- and micronutrients uptake of a sweet cherry cultivar cv. ’Katalin’ (Prunus avium L.) was studied according to apply different flower thinning techniques. Beside control treatment, three thinning treatments were performed: (I) thinning for I flower/inflorescence, (2) thinning for 2 flower/inflorescence, (3) thinning for 3 flower/inflorescence. Soil examination was carried out to establish the growing conditions of orchard site. Moreover, for studying the temporal dynamic of nutrient uptake plant analytical examination was performed four times per year based on leaf collecting according to the phenological phases. It was found that the macro- and micronutrients contents of leaves were showed significant differences between treatments before ripening, at ripening and after ripening stage. It was found that thinning has influence on mineral composition of leaf. Flower removal unbalanced the equilibrium of generative and vegetative processes. The applied manual flower thinning treatment resulted improving vegetative processes like nutrient uptake and storage.